Madrasah-based improvement management at MI Tarbiyah Islamiyah (Lembaga Pengembangan Kinerja Dosen, 2025)
In facing the challenges of globalization and the demands for improving the quality of education, madrasas, as Islamic elementary education institutions, are required to manage themselves inde-pendently and adaptively. This study aims to describe in detail the quality improvement manage-ment strategy based on madrasa management at MI Tarbiyah Islamiyah, analyze the supporting and inhibiting factors in its implementation, and formulate relevant and applicable alternative strategies for quality enhancement. This research uses a descriptive qualitative approach with data collection techniques including in-depth interviews, field observations, and document studies. The main informants consist of the head of the madrasa, a senior teacher, and the head of the madrasa committee. The results show that MI Tarbiyah Islamiyah implements quality management through participatory planning, the implementation of programs based on local needs, continuous evalua-tion, and strategic follow-up actions. Supporting factors include visionary leadership, teacher training, and active involvement of the madrasah committee. Meanwhile, the main obstacles are limited human resources, operational funding, and the utilization of technology. This study high-lights the importance of collaborative leadership, a quality-oriented work culture, and local adapta-tion in the sustainable implementation of madrasah-based quality improvement management.